2023
DOI: 10.1007/s12671-023-02161-0
|View full text |Cite
|
Sign up to set email alerts
|

Do Meditation, Mindfulness, and Self-Compassion Impact Utilitarian Moral Judgment?

Abstract: Objectives Meditation practices, mindfulness, and self-compassion have been found to affect our physical and mental well-being in many ways. However, can they also affect our moral judgment, for example, what we think about right and wrong? This study aims to explore the potential influence of meditation, mindfulness and self-compassion on utilitarian moral judgments. Method In Study 1 (n = 316), we measured participants’ frequency of meditation, their lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…The results suggested that as the university classification improved, MI, psychological resources, and MP increased, while IA decreased. These findings align with previous research, indicating that sociodemographic factors, such as university classification, significantly affect the well-being of university students [ 8 , 15 , 69 ]. However, it is worth noting that the literature presents inconsistent findings, emphasizing the need for further research to gain a more comprehensive understanding of these relationships and differences.…”
Section: Discussionsupporting
confidence: 91%
“…The results suggested that as the university classification improved, MI, psychological resources, and MP increased, while IA decreased. These findings align with previous research, indicating that sociodemographic factors, such as university classification, significantly affect the well-being of university students [ 8 , 15 , 69 ]. However, it is worth noting that the literature presents inconsistent findings, emphasizing the need for further research to gain a more comprehensive understanding of these relationships and differences.…”
Section: Discussionsupporting
confidence: 91%
“…If these results seem to demonstrate consistent construct validity of the OUS, other findings may raise questions regarding the complementarity of these two dimensions. While a number of studies have shown a positive correlation between the OUS-IB and OUS-IH scores (e.g., Kahane et al, 2018, study 2;Paruzel-Czachura & Kocur, 2023;Park et al, 2023;Navajas et al, 2021), others did not find a significant correlation between them (Filiz & Hasan, 2021;Kahane et al, 2018, study 1). Such results could mean that the two dimensions are related but distinct constructs, and play different roles in the influence of moral judgment.…”
Section: A New Tool: the Ousmentioning
confidence: 96%
“…The literature states that practising mindfulness helps improve reflection and understanding of emotions and mental events and leads to a higher capacity for objectivity regarding personal experiences (Eidman et al 2022). Additionally, research suggests that meditation influences peoples' morality (Feruglio et al 2022;Paruzel-Czachura & Kocur 2023), though with mixed results (Du et al 2023;Reynolds et al 2023).…”
Section: Mindfulnessmentioning
confidence: 99%